A CASE STUDY OF REDTONE INTERNATIONAL BERHAD - Yajid, Mohd Shukri Ab; kKhatibi, Ali; Johar,; MGM, (International Journal of Psychosocial Rehabilitation, 2020)
Emerging tier-2 telcos are making a big impact on the Malaysian telecommunications industry. They are capitalising on new technologies to provide traditional services such as voice calls which are much cheaper than services being offered on existing technology platforms. Creative pricing and packaging are also factors which favour these tier-2 telcos. The objective of this case study is to examine and understand the Malaysian tier-2 telco industry with special focus on Redtone International Berhad and its position in the market place. This case study will analyse the tier-2 telcos industry and operating environment. It will identify the business model of Redtone International Berhad and its strategies of product development, marketing and competition with tier-1 telcos. Focus will also be on Redtone’s value proposition and how it capitalises on emerging technologies to its advantage. This case study also proposes implementation plans for Redtone to undertake in order to maintain its leading position in Malaysia and also to be regional and global player in the voice call industry. The purpose of this plan is also to offset the shrinking local market share with revenue streams from abroad.